The Coping Strategy and Subjective Well-Being of Indonesian Families amid the Covid-19 Pandemic - Simanjuntak, Megawati; Muflikhati, Istiqlaliyah; Yuliati, Lilik Noor; Johan, Irni Rahmayani (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Due to the COVID-19 pandemic, economic pressures have forced families to make various adjustments to maintain their well-being. This study investigated economic coping strategies and the subjective well-being of families during the COVID-19 pandemic. A total of 1,125 families in Indonesia participated in an online survey using Google Forms and spoke through social media. The research shows that families experienced a decrease in income, which encouraged them to adopt various economic coping strategies. The coping strategy adopted was cutting expenses while increasing income, mainly by utilizing hobbies or skills. Income changes, education, poverty status, savings withdrawal, selling or pawn assets, asking for aid, and borrowing money significantly influenced subjective well-being. Differences in subjective well-being can be observed in economic status, education level, and changes in income. Changes in income and higher education positively affected subjective well-being. Poverty status also had a negative effect on subjective well-being negatively.